Engaging the Culture, Changing the World: The Christian University in a Post-Christian World - Glanzer, Perry L. (A journal of church and state, 2012)
In this volume, Philip Eaton, president of Seattle Pacific University, adds to the growing literature addressing Christian higher education. Eaton's book proves original in that he spends little time conversing with this literature. Instead, he attempts to set forth his own unique vision regarding the role of a Christian university in a post-Christian culture., This role, he believes, is important because the contemporary secular university proves deficient in a variety of ways. It lacks coherence because it provides no compelling or unifying story to guide us. Thus, we should not be surprised that the secular university is both losing its cultural influence and jettisoning the task of moral formation.